2008
DOI: 10.1021/ja800265s
|View full text |Cite
|
Sign up to set email alerts
|

18O Kinetic Isotope Effects in Non-Heme Iron Enzymes: Probing the Nature of Fe/O2 Intermediates

Abstract: Reported here are the competitive 18 O/ 16 O kinetic isotope effects ( 18 O KIEs) on k cat /K m (O 2 ) for three non-heme iron enzymes that activate O 2 at an iron center coordinated by a 2-His-1-carboxylate facial triad: taurine dioxygenase (TauD), S-(2)-hydroxypropylphosphonic acid epoxidase (HppE), and 1-aminocyclopropyl-1-carboxylic acid oxidase (ACCO). The comparison of the measured 18 O KIEs with calculated 18 O equilibrium isotope effects ( 18 O EIEs) reveals an excellent correlation with the proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 24 publications
7
102
0
Order By: Relevance
“…Our calculations revealed that the nucleophilic attack of the distal O atom of the O 2 adduct on the carbonyl group in αKG via a bicyclic transition state (TS1) is the rate-limiting step, which is between the addition of O 2 to the enzyme:Fe II /αKG/substrate complex and the generation of the Fe IV –oxo intermediate, as confirmed by recent experimental studies. [40] Decay of 7 TS1 affords a HS Fe III bound to an oxyl radical, whereas 5 TS1 evolves into a HS Fe II chelated by peroxosuccinate. According to the calculated energetics using DFT and ab initio methods, the septet reaction pathway might compete with the quintet channel.…”
Section: Discussionmentioning
confidence: 99%
“…Our calculations revealed that the nucleophilic attack of the distal O atom of the O 2 adduct on the carbonyl group in αKG via a bicyclic transition state (TS1) is the rate-limiting step, which is between the addition of O 2 to the enzyme:Fe II /αKG/substrate complex and the generation of the Fe IV –oxo intermediate, as confirmed by recent experimental studies. [40] Decay of 7 TS1 affords a HS Fe III bound to an oxyl radical, whereas 5 TS1 evolves into a HS Fe II chelated by peroxosuccinate. According to the calculated energetics using DFT and ab initio methods, the septet reaction pathway might compete with the quintet channel.…”
Section: Discussionmentioning
confidence: 99%
“…Metal binding was examined by isothermal titration calorimetry [84]. 18 O-kinetic isotope effect measurements were used to identify the first irreversible reaction of O 2 activation, the step following Fe(III)-superoxo formation [85]. It also has proven useful to supplement these experimental results with computational approaches, such as quantum mechanics/molecular mechanics and density functional theory calculations [57, 8693], and by comparison to biomimetic models [94, 95].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…To study the reactive oxygen species more closely, the 18 O KIE on k cat / K m(O2) for the reaction with native substrate, ( S )-HPP, was measured to be 1.0120, the magnitude of which is consistent with the formation of an [Fe III -OOH] species in the rate-determining step. 219 Formation of the Fe III -OOH species could involve direct hydrogen atom abstraction from the substrate ( 150 → 153 ). It may also be generated via a rate-limiting proton coupled electron transfer to form a ferric peroxy intermediate (151) that is then used to oxidize substrate directly ( 151 → 154 ), 220 or to form an [Fe IV =O] species which oxidizes substrate ( 151 → 152 → 155 ).…”
Section: Epoxide Biosynthesismentioning
confidence: 99%